Measurement of Individual Doses of Radiation by Personal Dosimeter Is Important for the Return of Residents from Evacuation Order Areas after Nuclear Disaster - Orita, Makiko (PLoS One, 2015)
To confirm the availability of individual dose evaluation for the return of residents after the accident at the Fukushima Dai-ichi Nuclear Power Plant (FNPP), we evaluated individual doses of radiation as measured by personal dosimeters in residents who temporarily stayed in Evacuation Order Areas in Kawauchi village, which is partially located within a 20 km radius of the FNPP. We also compared individual doses with the external radiation doses estimated from the ambient dose rates and with doses estimated from the concentrations of radionuclides in the soil around each individual’s house. Individual doses were significantly correlated with the ambient doses in front of the entrances to the houses (r = 0.90, p<0.01), in the backyards (r = 0.41, p<0.01) and in the nearby fields (r = 0.80, p<0.01). The maximum cumulative ambient doses in the backyards and fields around the houses were 6.38 and 9.27 mSv/y, respectively. The maximum cumulative individual dose was 3.28 mSv/y, and the median and minimum doses were 1.35 and 0.71 mSv/y. The estimated external effective doses from concentrations of artificial radionuclides in soil samples ranged from 0.03 to 23.42 mSv/y. The individual doses were moderately correlated with external effective doses in the backyards (r = 0.38, p<0.01) and in the fields (r = 0.36, p<0.01); however, the individual doses were not significantly correlated with the external effective doses in front of the entrances (r = 0.01, p = 0.92). Our study confirmed that individual doses are low levels even in the evacuation order area in Kawauchi village, and external effective dose levels are certainly decreasing due to the decay of artificial radionuclides and the decontamination of contaminated soil. Long-term follow-up of individual doses as well as internal-exposure doses, environmental monitoring and reconstruction of infrastructure are needed so that residents may return to their hometowns after a nuclear disaster.